Revisiting an ancient legend: influence of the lunar cycle on occurrence of first‐ever unprovoked seizures. Issue 6 (31st May 2022) - Wang, Shuyu; Boston, Ray; Lawn, Nicholas; Seneviratne, Udaya
Abstract: Background: The mythical effect of the lunar cycle on seizures has been debated over time. Previously healthy individuals presenting with first‐ever seizures in whom investigations are negative often invoke questions about potential reasons including a full moon. Aims: To determine whether there is a temporal relationship between the occurrence of the first‐ever unprovoked seizure and the lunar cycle. Methods: We studied adults who presented with a first‐ever unprovoked seizure to two tertiary centres in Australia. Seizure onset time was obtained from the emergency department and ambulance documentations. We used Poisson regression modelling and incidence rate ratios (IRR) to determine whether seizures have a preponderance for a particular lunar phase. We performed further analysis on 'first seizure epilepsy' and 'first seizure not epilepsy' subgroups based on the International League Against Epilepsy criteria for a diagnosis of epilepsy after a single unprovoked seizure. Results: We analysed 1710 patients (38% females; median age 39 years), of whom 18% had epileptiform abnormalities on electroencephalogram (EEG) and potentially epileptogenic lesions were detected on neuroimaging in 28%. Based on the EEG and imaging findings, 684 (40%) patients were categorised as 'first seizure epilepsy' and 1026 (60%) 'first seizure not epilepsy'. The whole cohort and subgroup analysis demonstrated no significant difference in the seizure occurrence among the four lunar quarters. Conclusions: First unprovoked seizures are not influenced by the lunar cycle. Patients pondering the cause of their first‐ever unprovoked seizure can be reassured that the full moon was not responsible.